IMPLEMENTATION OF GOVERNMENT POLICY TO INCREASE PARTICIPATION IN FORMAL EDUCATION AT WEGGEBINO PUBLIC JUNIOR HIGH SCHOOL, WEGEBINO DISTRICT, PANIAI REGENCY - Mathias Gobay; Kaharuddin Kaharuddin; Lukman Ismail (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the implementation of government education policies, especially the School Operational Assistance Fund (BOS) and the Smart Indonesia Program (PIP), as well as their impact on increasing the participation of formal education of students at Weggebino State Junior High School, Wegebino District, Paniai Regency. In addition, this study identifies supporting and inhibiting factors in the implementation of education policies in remote areas. The research uses a qualitative approach with a focus on the effectiveness of policy implementation and its impact on educational participation indicators, including student enrollment, attendance, and retention. The results of the study show that the implementation of education policy is partial. BOS funds are distributed quickly and regularly so that they are able to ensure the sustainability of school operations, supported by the availability of human resources and smooth internal administration. The Indonesia Pintar program has proven to contribute positively to increasing student attendance, especially for students from underprivileged families. In terms of impact, education policies and school performance in general have succeeded in increasing the number of new student enrollments, which reflects increasing public trust in formal educational institutions. However, the effectiveness of the policy is still limited by a number of inhibiting factors, especially the limitations of physical school facilities such as desks and chairs, geographical access and transportation barriers that have an impact on the delay in student attendance, and the absence of physical assistance in the form of books and learning tools. On the other hand, strong support from parents and the community as well as the smooth internal administration of the school are the main supporting factors for the successful implementation of education policies at Weggebino State Junior High School.